Severe progressive scoliosis in an adult female possibly secondary thoracic surgery in childhood treated with scoliosis specific Schroth physiotherapy: Case presentation. Issue 2 (October 2016) - Lebel, Andrea; Lebel, Victoria
Abstract Background Scoliosis is a complex three-dimensional (3D) spinal deformity. Acquired scoliosis in early childhood may progress into adulthood and pose an increased risk of health problems and reduction in quality of life. In Canada, patients with scoliosis are not referred for physiotherapeutic scoliosis-specific exercises (PSSE) despite the fact that Schroth physiotherapy, a scoliosis-specific 3D posture training and exercise program, can be effective in reducing pain and improving scoliosis curves, vital capacity, and overall quality of life in scoliosis patients. This case presentation shows that indeed adult curve progression can be stopped and even reversed with scoliosis specific Schroth physiotherapy (SSSPT) in an adult patient with scoliosis. Methods This is a retrospective case presentation involving a 23-year-old female scoliosis patient who began an outpatient Schroth physiotherapy exercise program and was initially monitored monthly and then annually for improvement in measurements of angle of trunk rotation (ATR) and chest expansion and improvement in vital capacity measured with incentive spirometry. Photos were taken to document body image periodically throughout Schroth physiotherapy treatment. Additionally, the patient completed SRS-22 quality of life questionnaires every 2 years to evaluate daily function, pain, self-imagine, mental health, and scoliosis management satisfaction. Results Within one month of beginning SSSPT, the patient reported no more back pain and within 2 months, reported improved breathing. The patient also benefitted from improved chest expansion, reduced scoliosis curve angles (measured in Cobb degrees), increased vital capacity, decreased ATR, and higher SRS-22 scores. She became more active and resumed all athletic activity within 8 months of beginning Schroth physiotherapy. Conclusions Adult scoliosis patients are not routinely referred for PSSE in Canada, even though Schroth physiotherapy, a form of PSSE, is shown to be effective in this case presentation. The patient in this case presentation was successfully treated with Schroth physiotherapy. Long-term comprehensive Schroth physiotherapy, to help correct and maintain proper posture in all aspects of daily living, should be part of scoliosis management for adult scoliosis patients in Canada to stop and reverse curve progression and to improve overall quality of life.